Geometries and Electronic States of Divacancy Defect in Finite-Size Hexagonal Graphene Flakes - Lili Liu; Shimou Chen (Journal of Chemistry)
The geometries and electronic properties of divacancies with two kinds of structures were investigated by the first-principles (U) B3LYP/STO-3G and self-consistent-charge density-functional tight-binding (SCC-DFTB) method. Different from the reported understanding of these properties of divacancy in graphene and carbon nanotubes, it was found that the ground state of the divacancy with 585 configurations is closed shell singlet state and much more stable than the 555777 configurations in the smaller graphene flakes, which is preferred to triplet state. But when the sizes of the graphene become larger, the 555777 defects will be more stable. In addition, the spin density properties of the both configurations are studied in this paper.